Pengaruh Model Information, Motivation, and Behavioral Skills (IMB) dalam Meningkatkan Deteksi Dini Kanker Serviks - Furi Estie Honez; Imami Nur Rachmawati (Journal of Telenursing (JOTING), 2023)
This research aims to examine the influence of the IMB Model (Information Motivation and Behavioral Skills Model) in increasing early detection of cervical cancer. The research method is by conducting a systematic search using four databases, namely, Proquest, Pubmed, Taylor & Francis, Sage Journals using journal search limits between 2012-2022, in English which focuses on interventions in increasing early detection of cervical cancer. Results: The IMB (Information Motivation and Behavioral Skills Model) intervention was considered effective in raising awareness of early detection of cervical cancer. Conclusion, the IMB model is effective in preventing HPV related cervical cancer. This intervention can be applied to low-middle income countries as an efficient and low cost national prevention program. Keywords: Early detection, Cervical cancer, Model Information Motivation and Behavioral Skills Model(IMB)